Design and characteristics of low‐resistance lithium‐ion battery pack and its fast charging method for smart phones. (28th July 2021) - Kim, Gi Young; Park, Seok Ryun; Yu, Jae Su
Summary: In order to apply fast charging in 5th generation (5G) mobile telecommunication, smart phones need to be used at higher current. As the resistance of battery pack increases, the charging time, heat generation, and capacity loss increase in proportion to the charging/discharging current. Thus, a low resistance battery pack is essential. Herein, we proposed a new lithium (Li)‐ion battery pack consisting of a low‐resistance battery cell and protection circuit module (PCM) for Galaxy S10 5G application. The battery cell reduced current density and resistance by loading level of active material and electrode thickness. The resistance of PCM was also reduced by employing low‐resistance circuit components and printed circuit board. It lowered resistance to 51 mΩ compared to 71 mΩ of the battery pack for Galaxy S10. For 5G mobile telecommunication and 25 W fast charging, the charging current should be increased from 3 to 5.7 A and the width of the PCM should be increased 2.45 times, but the low‐resistance components and optimization pattern design maintain 2.9 mm PCM width without decreasing capacity of battery pack. The experiment results showed that reducing the resistance of the battery pack by 26 mΩ reduced full charging time by 27 minutes and increased discharging time by 1 minute. The low‐resistance battery pack met the standard of UL2054 and heating temperature of smart phone. The optimal charging method was also proposed by comparing the charging capacity, charging time, and heat generation by charging current. The proposed charging method reduced the existing 153 minutes of full charging time to 126 minutes. The smart phone with low‐resistance battery pack was able to manage the maximum heating temperature below 43.1°C when charging with a 25 W charger. In addition, 0.2 C discharging capacity was 99.3% (4369.5 mAh) compared to the initial capacity after 400 cycles. After 400 cycles, the direct current internal resistance of the battery pack increased, but no Li precipitation was observed on the electrode. This could be applied to a smart phone employing Samsung Electronics' first 1.3 C fast charging for Galaxy S10 5G in the world's first 5G mobile telecommunication.